Microbiological and chemical safety of fruit drinks sold in Iloilo city - Gonzaga , Rochelle delos Reyes (2003.)
Fruit drinks collected from four selected sources, identified as A, B, C, and D in Iloilo City were subjected to microbiological analyses.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fruit drinks